Experimental study on the influence of wall heat effect on gas explosion and its propagation. (25th May 2017) - Ye, Qing; Wang, Geoff G.X.; Jia, Zhenzhen; Zheng, Chunshan
Abstract: In order to understand the mechanism and the influence degree of wall heat effect on gas explosion and its propagation, the influence of wall heat effect on gas explosion and its propagation is theoretically analyzed mainly from perspectives of the heat transportation and reaction process. Results show that the influence of wall heat loss on gas explosion strength is significant. In addition, the influences of wall heat effect on explosion wave and flame propagation velocity in the gas explosion process are experimentally investigated in the adiabatic condition and heat conduction. It is found that the wall heat effect can affect gas explosion strength, flame propagation velocity, peak overpressure and the peak flame propagation velocity, and their influence degree becomes more significant with the increase of the adiabatic degree. Therefore, it can be seen that the wall heat effect has an important influence on the gas explosion and its propagation. The influence of wall adiabatic condition on gas explosion with a higher combustion level is greater than the influence on gas explosion with low combustion levels.